The Effects of an Automatic Flushing Valve on the Hydraulic Performance of a Subsurface Drip Irrigation System for Alfalfa - Zaiyu Li; Yan Mo; Feng Wu; Hao Gao; Ronglian Wang; Jiandong Wang (Agriculture)
The automatic flushing valve (AFV) enables automatic flushing of drip irrigation systems, improving their anti-clogging performance. This study focuses on a subsurface drip irrigation system (SDI) for alfalfa, selecting T20 and T70 AFVs (with designed flushing durations of 20 and 70 s, respectively) installed at the end of the dripline and a buried dripline without an AFV as a control. The aim of this study was to explore the variations in AFV hydraulic performance over two years of operation and the impact on the irrigation uniformity of SDI systems. The results revealed that the flushing duration (FD) and flushing water volume (FQ) of both T20 and T70 fluctuated over time, with an average coefficient of variation (CV) of 13.2%. The FD and FQ of the two types of AFVs are affected by the daily average temperature (T), and when T increases from 20.1 °C to 25.7 °C, the FD and FQ increased by an average of 22.6%. After 2 years of operation, the average relative flow rate (Dra) and irrigation uniformity (Cu) of the T20 and T70 SDI emitters were 93.7% and 96.8%. Both the Dra and Cu were significantly influenced by FD (p < 0.05). Compared with CK and T20, T70 significantly increased the Dra and Cu by 6.3% and 4.6%, respectively. The order of degree of clogging at different positions in the dripline was rear > middle > front for the CK and T20 treatments, whereas for T70, it was middle > front > rear. With the installation of the T70 AFV, the time required for the SDI system to reach moderate clogging (Dra = 50~80%) was extended from 3~7 years to 8~20 years, resulting in a 180% increase in operation time. The T70 AFV is recommended for use in the alfalfa SDI of this study.